Adopsi Teknologi pada Pesantren Menuju Generasi Rabbani: - - Nur Indah Nopriska Rizaldi; Ananda Sekar Putri; Muh. Azra Fajriansyah; Zahra Luthfiah (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
Education is an absolute necessity for every generation. Therefore, to support these needs, educational institutions such as schools were established that organize teaching and learning activities. Pesantren is one type of educational institution with the same equivalence as public schools. Of course, this pesantren has several differences from schools in general, one of which is by emphasizing religious teachings so that the relationship between humans and God is based on the Qur'an and sunnah. By doing so, it is hoped that this pesantren will create a superior rabbinic generation. Of course, to create a superior generation of Rabbani, we are faced with various challenges, one of which is the increasingly rapid development of technology. The development of technology is increasingly rapid, resulting in every component in life including education, it's just that some Islamic boarding schools that still have not implemented technology, although there is also a positive side of technology to boarding schools should also be able to participate in implementing technology to develop and improve quality education to create a Rabbani generation